Flavour and energy dependence of chemical freeze-out temperatures in relativistic heavy ion collisions from RHIC-BES to LHC energies - Fernando Antonio Flor (Physics Letters B, 2021)
We present calculations of the chemical freeze-out temperature (Tch) based on particle yields from STAR and ALICE measured at collision energies ranging from sNN= 11.5 GeV to 5.02 TeV. Employing the Grand Canonical Ensemble approach using the Thermal-FIST Hadron Resonance Gas model package, we show evidence for a flavour-dependent chemical freeze-out in the crossover region of the QCD phase diagram. At a vanishing baryochemical potential, we calculate light and strange flavour freeze-out temperatures TL=150.2±2.6 MeV and TS=165.1±2.7 MeV, respectively.